Multiple sources of reproductive isolation in a bimodal butterfly hybrid zone (2010)
An important evolutionary question concerns whether one or many barriers are involved in the early stages of speciation. We examine pre? and post?zygotic reproductive barriers between two species of butterflies (Heliconius erato chestertonii and H.?e.?venus ) separated by a bimodal hybrid zone in the Cauca Valley, Colombia. We show that there is both strong pre? and post?mating reproductive isolation, together leading to a 98% reduction in gene flow between the species. Pre?mating isolation plays a primary role, contributing strongly to this isolation (87%), similar to previous examples in Heliconius . Post?mating isolation was also strong, with absence of Haldane’s rule, but an asymmetric reduction in fertility (<?11%) in inter?specific crosses depending on maternal genotype. In summary, this is one of the first examples of post?zygotic reproductive isolation playing a significant role in early stages of parapatric speciation in Heliconius and demonstrates the importance of multiple barriers to gene flow in the speciation process.